Coderspeak: The language of computer programmers - Orlandini Heurich, Guilherme (UCL Press, 2024)
Software applications have taken over our lives. We use and are used by software many times a day. Nevertheless, we know very little about the invisibly ubiquitous workers who write software. Who are they and how do they perceive their own practice? How does that shape the ways in which they collaborate to build the myriad of apps that we use every day? Coderspeak provides a critical approach to the digital transformation of our world through an engaging and thoughtful analysis of the people who write software. It is a focused and in-depth look at one programming language and its community – Ruby - based on ethnographic research at a London company and conversations with members of the wider Ruby community in Europe, the Americas and Japan. This book shows that the place people write code, the language they write it in and the stories shared by that community are crucial in questioning and unpacking what it means to be a ‘coder’. Understanding this social group is essential if we are to grasp a future (and a present) in which computer programming increasingly dominates our lives. Praise for Coderspeak 'Heurich perfectly captures the generous camaraderie, quirky spirit and intellectual curiosity at the heart of the Ruby world. Packed with tidbits of Ruby history, code snippets, and fascinating conversations, this book has something to teach every Rubyist.' Jemma Issroff, Ruby Core Team